From antiferromagnetism to field-induced ferromagnetism: A Cu2+-governed metamagnetic landscape in RFeCuGe4O12 (R = Tm-Lu) - Xu, Diming; Liu, Zhibo; Li, Xiao; Avdeev, Maxim; Zhou, Ke-Hong; Li, Jun; Tan, KarBan; Meng, Yin-Shan (Royal Society of Chemistry, 2025)
Metamagnetism represents a distinctive subclass within the antiferromagnetic (AFM) regime, exhibiting significant potential for diverse technological applications, particularly in magnetocaloric effects. In this paper, we systematically investigate the magnetic-field-induced phase transition in RFeCuGe4O12 (R = Tm-Lu) through comprehensive temperature-dependent and field-dependent magnetization measurements and neutron powder diffraction (NPD) analysis. Our experimental results demonstrate an AFM transition at ∼18, 13 and 13.5 K of Tm, Yb and Lu, respectively, but the magnetic-field-induced phase transition was only seen in Tm at ∼1.8 T (2 K). NPD refinements elucidate that the metamagnetic transition corresponds to A-type antiferromagnetic ordering at zero-field and a ferromagnetic (FM) structure emerges under high magnetic fields, with magnetic moments aligned along the c-axis; for R = Yb and Lu, A + G-type AFM and A + C-type AFM structures were observed. Our findings suggest that the anisotropic cation Cu2+ plays a crucial role in mediating the metamagnetic behavior, while the A-site cation significantly influences the internal molecular field and subsequently the metamagnetic behavior. These results provide valuable insights into the fundamental mechanisms governing metamagnetic transitions in complex oxide systems or multimetallic oxide systems.